New Zealand Pae Ora Healthcare Reforms 2022: Viable by Design? A Qualitative Study Using the Viable System Model - Akmal, Adeel; Podgorodnichenko, Nataliya; Gauld, Robin; Stokes, Tim (International journal of health policy and management, 2023)
Background: The New Zealand (NZ) Pae Ora (Healthy Futures) health reforms came into effect in July 2022 with the establishment of Health New Zealand (HNZ) (Te Whatu Ora) and the Māori Health Authority (MHA) (Te Aka Whai Ora) – the organisations charged for healthcare provision and delivery. Given these changes represent major health system reform, we aimed to conduct an early evaluation of the design of the reforms to determine if they can deliver a viable and sustainable NZ health system going forward. Methods: The evaluation was informed by Beer’s viable system model (VSM). A qualitative exploratory design with semi-structured interviews and documents analysis using thematic analysis was used. We conducted 28 interviews with senior healthcare managers and reviewed over 300 official documents and news analyses. Results: The VSM posits that for a system to be viable, all its five sub-systems (operations; co-ordination; operational control; development and governance) need to be strong. Our analysis suggests that the health reforms, despite their strengths, do not satisfy this requirement. The reforms do appreciate the complexity of the healthcare environment: multiple stakeholders, social inequalities, interdependencies. However, our analysis suggests a severe lack of detail regarding the implementation and operationalisation of the reforms. Furthermore, resourcing and coordination within the reformed system is also unclear. Conclusion: The health system reforms may not lead to a viable future NZ health system. Poor communication of the reform implementation and operationalisation will likely result in system failure and inhibit the ability of frontline health organisations to deliver care.